Islamic Education Character Education Concepts - Roihatul Jannah (DIROSAT: Journal of Education, Social Sciences & Humanities, 2023)
Character education is a value that must be learned, felt, and applied in a child's daily life. The concept of character education in Indonesia is the education of noble values originating from Indonesian culture in the framework of developing the personality of the younger generation which includes three aspects, namely moral knowing, moral feeling, and moral acting. The concept of Islamic education is guidance given by someone to someone so that he can develop optimally in accordance with Islamic teachings concerning the development of the body, mind and heart of students. This study aims to determine the concept of character education according to the figures, and to determine the concept of character education from the perspective of Islamic education according to Abdul Majid. The type of this research is library research which is based on the study and review of the text. This is done because the data sources used are in the form of literature data which makes library materials the main data source. The conclusion of this study is character education is a characteristic that exists in a person and morals or character that distinguishes one person from another. The purpose of character education is to form human beings who have good morals, are tolerant, have morals and instill self-responsibility, and build an optimistic mentality in carrying out their lives. By instilling religious character values, honesty, tolerance, discipline, and hard work. Character education in an Islamic perspective contained in the book Character Education with an Islamic Perspective by Abdul Majid and Dian Andayani states that character education in an Islamic view is morals and morals in Islam are also called personality. Carry out the religious teachings adhered to according to the stage of child development, recognize one's own strengths and weaknesses, comply with social rules that apply in their environment, respect the diversity of religions, cultures, ethnicities, races and socio-economic groups in the surrounding environment, use information about the surrounding environment in a comprehensive manner. logical, critical and creative, demonstrating the ability to think logically, critically, and creatively with the guidance of a teacher/educator, demonstrating a high sense of curiosity and realizing its potential, demonstrating the ability to solve simple problems in everyday life.